As significações de coordenadores pedagógicos da rede SESI-SP sobre a sua atuação no processo de construção do projeto formativo de sua unidade escolar - Fernandes, Sebastião (2017)
This research aims to analyze the meanings of SESI-SP pedagogical coordinators about their performance on the process of construction of the formative project of their school unit. It intends, as deployment of the analysis, to present theorizations on the meanings about the coordinators practices that reveal professional development possibilities in the analyzed process. The research was fulfilled with SESI-SP pedagogical coordinators. This public was defined in view of the institution administrative division that splits its schools on 13 Strategic Areas of Service, and 11 of them accepted to take part on this research. The group works on the teachers’ formation of their units, in addition to having other assignments defined by SESI-SP, such as replacing the school principal on his/her absence. The task of developing the formative project was defined and guided by the Basic Educational Management, counting on the group participation of Pedagogical Coordinators trainers. The research data was produced by the application of questions elaborated intending to know their professional profile and their meanings about the development of their school units formative project. The data was grouped by the similarity and singularity of some answers. The Socio-Historical perspective was used as a base to analyze, along to theorists that sustain the formation and the professional development of trainers. The analysis highlights that the work with formative projects was pointed by the participants as a powerful tool for its practice to be effective on the teachers’ formation. However, they demonstrate the need of time and space formation enlargement for all the school, since only the ones that have full time education have been guarantying a weekly schedule of teachers’ formation. Another aspect revealed by the research was the contribution of the diagnosis of teacher formative needs so the coordinators could have more assertiveness on their interventions, but the participants alert to the fact the diagnostic tool was developed without the teachers. The participants understand they work in a unit of a group of schools and everybody should follow the same procedures, but they say it should have a bigger possibility of meeting local demands. The points highlighted by the analysis evidence the necessity of schools to be considered as pedagogical knowledge construction spaces, and for that to happen it needs to be established in a proper way to its necessities times and spaces to form all the professionals involved in the learning and teaching process